Sustainable enterprise strategies for optimizing digital stewardship a guide for libraries, archives, and museums - Fritz, Angela, 1968- (LITA guides, 2021)
"As most institutions contemplate an enterprise digital content strategy for a growing number of digitized surrogates and born-digital assets, libraries, archives, and museums understand that these expanding needs can only be met by more flexible approaches offered by a multicomponent digital asset management ecosystem (DAME)"--